SOCIAL POLICY MODELS AND MACRO SOCIAL WORK PRACTICE WITH IMMIGRANT POPULATIONS: RESPONSES TO PREJUDICES, RACISM AND DISCRIMINATION - Bornarova, Suzana (Ревија за социјална политика/Journal of Social Policy, 2016)
The population of immigrants and refugees is growing rapidly worldwide. This vulnerable population group often faces prejudice, racism and discrimination and impacts inter-ethnic relations in countries of destination. How these problems are being resolved in a society depends on the ideology upon which social policy is based, as well as on the commonly adopted concepts of human diversity. Social policy responses to disadvantage and discrimination based on these criteria, are described in the second chapter of this paper. On the other hand, social work is one of the professions which is likely to serve this vulnerable population group, when and where encountered. Although social work historically has been involved in service to immigrant populations, the professional response has been limited to micro social work practice and direct service delivery to individuals and families. Therefore, a specific focus in this paper will be given to highlighting the importance of macro social work methods used to improve inter-ethnic relations, to overcome prejudices and discrimination to contribute to the respect of human rights. Advocacy, lobbying, community development and community education will be in more detail elaborated to emphasize their importance into making social work matter, not only on micro and mezzo, but on macro levels as well.